Dual-energy Computed Tomographic Pulmonary Angiography Accurately Estimates Lobar Perfusion Before Lung Volume Reduction for Severe Emphysema. Issue 2 (19th March 2023) - Jeyin, Nidhish; Desai, Sujal R.; Padley, Simon P.G.; Wechalekar, Kshama; Gregg, Sima; Sousa, Tiago; Shah, Pallav L.; Allinson, James P.; Hopkinson, Nicholas S.; Begum, Sofina; Jordan, Simon; Kemp, Samuel V.; et al.
Abstract : Purpose: To assess if dual-energy computed tomographic pulmonary angiography (DECTPA) derived lobar iodine quantification can provide an accurate estimate of lobar perfusion in patients with severe emphysema, and offer an adjunct to single-photon emission CT perfusion scintigraphy (SPECT-PS) in assessing suitability for lung volume reduction (LVR). Materials and Methods: Patients with severe emphysema (forced expiratory volume in 1 s <49% predicted) undergoing evaluation for LVR between May 2018 and April 2020 imaged with both SPECT-PS and DECTPA were included in this retrospective study. DECTPA perfused blood volume maps were automatically segmented and lobar iodine mass was estimated and compared with lobar technetium (Tc99m) distribution acquired with SPECT-PS. Pearson correlation and Bland-Altman analysis were used for intermodality comparison between DECTPA and SPECT-PS. Univariate and adjusted multivariate linear regression were modelled to ascertain the effect sizes of possible confounders of disease severity, sex, age, and body mass index on the relationship between lobar iodine and Tc99m values. Effective radiation dose and adverse reactions were recorded. Results: In all, 123 patients (64.5±8.8 y, 71 men; mean predicted forced expiratory volume in 1 s 32.1 ±12.7%, ) were eligible for inclusion. There was a linear relationship between lobar perfusion values acquired using DECTPA and SPECT-PS with statistical significance ( P <0.001). Lobar relative perfusion values acquired using DECTPA and SPECT-PS had a consistent relationship both by linear regression and Bland-Altman analysis (mean bias, −0.01, mean r 2 0.64; P <0.0001). Individual lobar comparisons demonstrated moderate correlation ( r =0.79, 0.78, 0.84, 0.78, 0.8 for the right upper, middle, lower, left upper, and lower lobes, respectively, P <0.0001). The relationship between lobar iodine and Tc99m values was not significantly altered after controlling for confounders including symptom and disease severity, age, sex, and body mass index. Conclusions: DECTPA provides an accurate estimation of lobar perfusion, showing good agreement with SPECT-PS and could potentially streamline preoperative assessment for LVR.